Characteristics of electron transport chain and affecting factors for thiosulfate-driven perchlorate reduction. (October 2017) - Zhang, Chao; Guo, Jianbo; Lian, Jing; Lu, Caicai; Ngo, Huu Hao; Guo, Wenshan; Song, Yuanyuan; Guo, Yankai
Abstract: The mechanism for perchlorate reduction was investigated using thiosulfate-driven (T-driven) perchlorate reduction bacteria. The influences of various environmental conditions on perchlorate reduction, including pH, temperature and electron acceptors were examined. The maximum perchlorate removal rate was observed at pH 7.5 and 40 °C. Perchlorate reduction was delayed due to the coexistence of perchlorate-chlorate and perchlorate-nitrate. The mechanism of the T-driven perchlorate reduction electron transport chain (ETC) was also investigated by utilizing different inhibitors. The results were as follows: firstly, the NADH dehydrogenase was not involved in the ETC; secondly, the FAD dehydrogenase and quinone loop participated in the ETC; and thirdly, cytochrome oxidase was the main pathway in the ETC. Meanwhile, microbial consortium structure analysis indicated that Sulfurovum which can oxidize sulfur compounds coupled to the reduction of nitrate or perchlorate was the primary bacterium in the T-driven and sulfur-driven consortium. This study generates a better understanding of the mechanism of T-driven perchlorate reduction. Graphical abstract: Highlights: The optimum temperature 40 °C, pH 7.5 was obtained for perchlorate reduction. Perchlorate reduction was delayed in presence of NO3 − and ClO3 − . Complex I was not involved in electron transport process of T-driven ClO4 − reduction. Sulfurovum was the main bacterium in T-driven and S-driven consortium.